2013
DOI: 10.1177/2150137813494766
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis in Counseling Research and Practice

Abstract: This article summarizes the general uses and major characteristics of factor analysis, particularly as they may apply to counseling research and practice. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) are overviewed, including their principal aims, procedures, and interpretations. The basic steps of each type of factor analysis are elucidated. For EFA, the methods of factor extraction (principal component analysis and principal axis factoring), retention, rotation, and naming are sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 35 publications
2
155
0
6
Order By: Relevance
“…There is no complete agreement regarding interpretation of fit indices (Mvududu & Sink, 2013), but using relatively conservative criteria (four or lower for w 2 /df, 0.90 or higher for CFI and TLI; lower than 0.10 for RMR and lower than 0.08 for the RMSEA), all current indices fell within acceptable range. It has been reported that RMSEA may over-reject good models at small sample sizes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no complete agreement regarding interpretation of fit indices (Mvududu & Sink, 2013), but using relatively conservative criteria (four or lower for w 2 /df, 0.90 or higher for CFI and TLI; lower than 0.10 for RMR and lower than 0.08 for the RMSEA), all current indices fell within acceptable range. It has been reported that RMSEA may over-reject good models at small sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, four individuals (three men and one woman) were assigned and instructed to survey 25 women. Fundamentally, CFA is used to determine whether an instrument's factor structure derived from exploratory factor analytic approaches can hold up with another respondent sample (Mvududu & Sink, 2013). We used CFA to examine the previously identified factor structure of the scale (see Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…We computed two CFAs to test the construct validity of instrumentation prior to computing the HLR and MANOVA (Research Question 1). A maximum likelihood estimation method was used in both CFAs because the parametric properties of items were largely consistent (skewness and kurtosis values were approximately ±1) with normal distributions (Mvududu & Sink, 2013). We ensured that our sample size exceeded the requirements for computing CFA, with a 27:1 ratio of respondents to each estimated parameter (Mvududu & Sink, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In Section , the correlation among the 11 terrain factors has been computed so that the correlation matrix can be employed to examine suitability for factor analysis. Two quantitative methods, the KMO (Kaiser‐Meyer‐Olkin) index and Bartlett test of sphericity, are available in SPSS to examine the correlation matrix . The KMO index specifies how small the partial correlations are relative to the original correlations while Bartlett test of sphericity examines whether the terrain factors are highly uncorrelated or not.…”
Section: Factor Analysismentioning
confidence: 99%